Molecular versus exciton diffusion in fluorescence-based explosive vapour sensors. Issue 98 (14th October 2015) - Ali, M. A.; Geng, Y.; Cavaye, H.; Burn, P. L.; Gentle, I. R.; Meredith, P.; Shaw, P. E.
Abstract : Real time vapour detection efficiency is reliant on analyte diffusion rather than amplified fluorescence quenching processes based on exciton diffusion. Abstract : The diffusion of p -nitrotoluene vapours into polymer or dendrimer sensing films follows Super Case II dynamics in which the quenching efficiency is strongly correlated to an accelerating analyte front propagating through the neat film rather than being reliant on exciton diffusion.